Oat bran, but not its isolated bioactive β-glucans or polyphenols, have a bifidogenic effect in an in vitro fermentation model of the gut microbiota. Issue 5 (28th January 2019) - Kristek, Angelika; Wiese, Maria; Heuer, Patrizia; Kosik, Ondrej; Schär, Manuel Y.; Soycan, Gulten; Alsharif, Sarah; Kuhnle, Gunter G. C.; Walton, Gemma; Spencer, Jeremy P. E.
Abstract: Wholegrain oats are known to modulate the human gut microbiota and have prebiotic properties (increase the growth of some health-promoting bacterial genera within the colon). Research to date mainly attributes these effects to the fibre content; however, oat is also a rich dietary source of polyphenols, which may contribute to the positive modulation of gut microbiota. In vitro anaerobic batch-culture experiments were performed over 24 h to evaluate the impact of two different doses (1 and 3 % (w/v)) of oat bran, matched concentrations of β -glucan extract or polyphenol mix, on the human faecal microbiota composition using 16S RNA gene sequencing and SCFA analysis. Supplementation with oats increased the abundance of Proteobacteria ( P <0·01) at 10 h, Bacteroidetes ( P <0·05) at 24 h and concentrations of acetic and propionic acid increased at 10 and 24 h compared with the NC. Fermentation of the 1 % (w/v) oat bran resulted in significant increase in SCFA production at 24 h (86 (sd 27) v . 28 (sd 5) mm ; P <0·05) and a bifidogenic effect, increasing the relative abundance of Bifidobacterium unassigned at 10 h and Bifidobacterium adolescentis ( P <0·05) at 10 and 24 h compared with NC. Considering the β -glucan treatment induced an increase in the phylum Bacteroidetes at 24 h, it explains the Bacteriodetes effects of oats as a food matrix. The polyphenol mix induced an increase in Enterobacteriaceae family at 24 h. In conclusion, in this study, we found that oats increased bifidobacteria, acetic acid and propionic acid, and this is mediated by the synergy of all oat compounds within the complex food matrix, rather than its main bioactive β -glucan or polyphenols. Thus, oats as a whole food led to the greatest impact on the microbiota.